O cinema-performance fabulado por mulheres - Santos, Luíza Fonseca de Oliveira (2024)
This master's research aims to explore cinema-performance to think about these two languages in friction, reciprocally activating resources from these ways of thinking. We will especially focus on productions proposed by women. In this type of cinema, there is a protagonism of the body and performative procedures that challenge cinematic language itself, bringing it closer to performance and philosophy through fabulatory actions. The theoretical foundation is based on Greiner and Katz's corpusmedia theory, in addition to bringing together other authors who specifically analyze experimental cinema, such as Elena del Rio, Laura U. Marks and Martine Beugnet. The research corpus will be composed of the analysis of films by artists Maya Deren, Marina de Van and Ana Pi, as well as a practical experiment tested by myself, during my master's degree. As an analytical research strategy, we will focus on fabulatory action as proposed by Greiner (2017 and 2021) to understand the processes of political resistance